3D printed microchannel networks to direct vascularisation during endochondral bone repair. (April 2018) - Daly, Andrew C.; Pitacco, Pierluca; Nulty, Jessica; Cunniffe, Gráinne M.; Kelly, Daniel J.
Abstract: Bone tissue engineering strategies that recapitulate the developmental process of endochondral ossification offer a promising route to bone repair. Clinical translation of such endochondral tissue engineering strategies will require overcoming a number of challenges, including the engineering of large and often anatomically complex cartilage grafts, as well as the persistence of core regions of avascular cartilage following their implantation into large bone defects. Here 3D printing technology is utilized to develop a versatile and scalable approach to guide vascularisation during endochondral bone repair. First, a sacrificial pluronic ink was used to 3D print interconnected microchannel networks in a mesenchymal stem cell (MSC) laden gelatin-methacryloyl (GelMA) hydrogel. These constructs (with and without microchannels) were next chondrogenically primed in vitro and then implanted into critically sized femoral bone defects in rats. The solid and microchanneled cartilage templates enhanced bone repair compared to untreated controls, with the solid cartilage templates (without microchannels) supporting the highest levels of total bone formation. However, the inclusion of 3D printed microchannels was found to promote osteoclast/immune cell invasion, hydrogel degradation, and vascularisation following implantation. In addition, the endochondral bone tissue engineering strategy was found to support comparable levels of bone healing to BMP-2 delivery, whilst promoting lower levels of heterotopic bone formation, with the microchanneled templates supporting the lowest levels of heterotopic bone formation. Taken together, these results demonstrate that 3D printed hypertrophic cartilage grafts represent a promising approach for the repair of complex bone fractures, particularly for larger defects where vascularisation will be a key challenge.